2019
DOI: 10.1001/jama.2019.2210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation on Relapse-Free Survival Among Patients With Digestive Tract Cancers

Abstract: IMPORTANCE Randomized clinical trials of vitamin D supplementation for secondary prevention in patients with cancer are needed, given positive results of observational studies. OBJECTIVE To determine whether postoperative vitamin D 3 supplementation can improve survival of patients with digestive tract cancers overall and in subgroups stratified by 25-hydroxyvitamin D (25[OH]D) levels. DESIGN, SETTING, AND PARTICIPANTS The AMATERASU trial, a randomized, double-blind, placebo-controlled trial conducted at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 34 publications
2
131
0
Order By: Relevance
“…Vitamin D has been found to have antitumour effects, suggesting that it might inhibit the progression of rectal cancer 10 , breast cancer 11 , pancreatic cancer 12,13 , head and neck cancers 14 and other cancers. Urashima 15 suggested that the higher the serum level of vitamin D is, the better is the prognosis of rectal cancer patients. However, the effects of vitamin D in chemotherapy remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has been found to have antitumour effects, suggesting that it might inhibit the progression of rectal cancer 10 , breast cancer 11 , pancreatic cancer 12,13 , head and neck cancers 14 and other cancers. Urashima 15 suggested that the higher the serum level of vitamin D is, the better is the prognosis of rectal cancer patients. However, the effects of vitamin D in chemotherapy remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…(9) In addition, two recent RCTs suggest that patients with digestive tract cancers, especially colorectal cancer, may benefit from vitamin D supplementation. (47,48) Our findings indicate that the assessment of vitamin D status using bioavailable instead of total 25OHD levels would aid in the identification of individuals who are most likely to benefit from vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 93%
“…In this post hoc analysis using residual serum samples and clinical data from the AMATERASU trial, we aimed to explore whether vitamin D supplementation improved survival in a subgroup of patients with lower than median levels of bioavailable 25(OH)D. Table 1 shows the characteristics of the participants analyzed in this post hoc study. The distribution of variables was similar to the original trial [5]. All patients were Japanese.…”
Section: Introductionmentioning
confidence: 59%
“…A meta-analysis of 16 prospective cohort studies including more than 100,000 patients showed that higher total 25(OH)D levels in serum were significantly associated with decreased cancer-specific mortality [4] independent of cancer site or pathological subtype. However, contrary to expectations, recent randomized clinical trials (RCTs) have demonstrated that vitamin D supplementation, compared with placebo, did not result in significant improvement of relapse or progression-free survival among the total study population or a subgroup of patients with low total 25(OH)D levels (<20 ng/mL) in digestive tract cancer [5] and advanced or metastatic colorectal cancer [6].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation